2022
DOI: 10.1021/acs.energyfuels.1c04004
|View full text |Cite
|
Sign up to set email alerts
|

Reducing NOx Emission of Swirl-Stabilized Ammonia/Methane Tubular Flames through a Fuel-Oxidizer Mixing Strategy

Abstract: Ammonia as a fuel can be a carbon-free and longduration scalable hydrogen energy carrier. In the carbon-neutral power system, co-firing ammonia with natural gas is a promising technique for flexible operations of gas turbines and gas-fired boilers. However, the NO x propensity of ammonia/methane flames is a severe problem under global fuel-lean conditions. This work has investigated the NO x performance of various fueloxidizer mixing strategies on a tangential swirl burner. We propose a new ammonia co-combusti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Ammonia serves as a refrigerant in large industrial refrigerators and is a key component of fertilizers and various industrial goods. In recent years, ammonia has been considered as a potential alternative fuel and hydrogen storage carrier in power systems and energy storage due to its carbon-free nature and high hydrogen density. Due to its excellent thermal properties, ammonia is well suited for large-scale storage and transportation. , In addition, ammonia is a highly toxic chemical that can cause environmental pollution and injury if accidentally burned or exploded. The lower molecular weight of ammonia allows for faster diffusion compared with ambient air. During the storage, transport and bunkering of ammonia as well as hydrogen production during ammonia cracking, ammonia leakage in the high-pressure storage containers and hitting ignition sources can lead to explosions, structural damage to buildings, and destruction of production facilities, endangering personal safety .…”
Section: Introductionmentioning
confidence: 99%
“…Ammonia serves as a refrigerant in large industrial refrigerators and is a key component of fertilizers and various industrial goods. In recent years, ammonia has been considered as a potential alternative fuel and hydrogen storage carrier in power systems and energy storage due to its carbon-free nature and high hydrogen density. Due to its excellent thermal properties, ammonia is well suited for large-scale storage and transportation. , In addition, ammonia is a highly toxic chemical that can cause environmental pollution and injury if accidentally burned or exploded. The lower molecular weight of ammonia allows for faster diffusion compared with ambient air. During the storage, transport and bunkering of ammonia as well as hydrogen production during ammonia cracking, ammonia leakage in the high-pressure storage containers and hitting ignition sources can lead to explosions, structural damage to buildings, and destruction of production facilities, endangering personal safety .…”
Section: Introductionmentioning
confidence: 99%
“…Attempts have been made to address the various challenges in using ammonia as a fuel. ,,, For instance, with swirling combustion which is helpful to enhance flame intensity via recirculating reactive radicals and increasing the reaction residence time, researchers have been able to stabilize ammonia flames over a wide range of conditions. , More recently, particular attention has also been given to the mitigation of the high fuel NO x emission in ammonia flames. Nevertheless, regardless of the accomplishments, there is still a need for a better understanding and control of the NO x emission of ammonia flames in various specific scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Ammonia (NH 3 ) is an emerging carbon-free fuel, which could be produced either by fossil fuels via a matured Haber–Bosch process coupled with carbon capture and storage facilities (CCS) or by those green hydrogen (H 2 ) from electrolysis of water with renewable electricity (e.g., wind power and solar power). In this way, ammonia is deemed as a hydrogen carrier and renewable fuel and as novel carbon-free alternative fuel for various engines (e.g., compression ignition engine and gas turbine), fuel cells, and industrial furnaces. ,, Co-firing coal with ammonia in power station boilers was first proposed by Japan in 2014 , and recently is gaining more attention worldwide. ,− Existing studies on ammonia–coal co-firing primarily investigate the formation and emission characteristics of NO x considering the extra introduction of massive fuel nitrogen contained in ammonia molecule. , A series of experimental studies have been carried out by CRIEPI (Central Research Institute of Electric Power Industry, Japan), IHI Corporation, , Hokkaido University, , and Osaka University on lab scale (e.g., 760 kW th ) and pilot scale (e.g., 1.2 MW th ) coal combustion apparatus, investigating the effects of ammonia co-firing ratio, ammonia injection position and parameters, co-firing mode with coal/air (e.g., premixed with coal stream and premixed with air stream), coal properties (e.g., volatile matter content), and air staging on the formation and emission of NO and N 2 O. The results showed that emission of NO was not monotonically increased with increasing ammonia co-firing ratio, and reasonable organization of ammonia and coal stream could reduce the NO emission with ammonia co-firing (e.g., at a co-firing ratio of 10 cal.…”
Section: Introductionmentioning
confidence: 99%